Five Years In: The AAOS Resident Assembly, "Bidirectional Communication, " and Early Career Involvement in Orthopaedic Leadership. Issue 14 (15th July 2022) - Fourman, Mitchell S.; Smith, Cory; Jensen, Andrew R.; Muzzonigro, Thomas; Woiczik, Marcella; Hogan, MaCalus V.
Abstract : Established in 2014, the American Academy of Orthopaedic Surgeons (AAOS) Resident Assembly (RA) has served as a mode of "bidirectional communication" between AAOS and a combined resident body. Training and education initiatives relevant to the current issues facing residency training can be passed up to and directly addressed by the leadership of AAOS, whereas AAOS recruitment and membership initiatives can be disseminated to the full resident body through the RA. Since its inception in 2014, the RA has grown markedly, with representation from most MD and DO residency programs in the United States and Canada. It also has included an increasing number of medical students from Orthopaedic Surgery Interest Groups to directly take part in RA activities. For the past half decade, the RA has served as a partner for the AAOS in addition to a valuable recruitment tool to engage the broadest diversity of potential orthopaedic leaders at their earliest stages of training. This work is a review of the development of the RA over its first half decade, as well as a discussion of its future goals in line with AAOS priorities.